A large cross‐sectional survey of COVID‐19 vaccination willingness amongst healthcare students and professionals: Reveals generational patterns. (17th March 2022) - Tomietto, Marco; Simonetti, Valentina; Comparcini, Dania; Stefanizzi, Pasquale; Cicolini, Giancarlo
Abstract: Aims: To determine coronavirus disease 2019 (COVID‐19) vaccination hesitancy in healthcare professionals and healthcare students in Italy across four generations (baby boomers, generations X, Y and Z). Design: A cross‐sectional descriptive study was performed through an online survey conducted from May to June 2021. The STROBE guidelines were adopted for reporting. Methods: Data were collected by initially sending a survey link to a convenience sample of healthcare professionals and students, which was followed by snowball sampling. The VAX scale was validated and adopted. An ANOVA was performed to detect differences in vaccine‐hesitancy beliefs between the four generational groups. Results: The survey was completed by 1226 healthcare professionals and students. Worries about unforeseen future effects accounted for the higher vaccination hesitancy factor across generations. More positive attitudes towards COVID‐19 vaccination were expressed by members of generation Z than by members of generation Y and baby boomers. Members of generation X had the highest vaccination hesitancy scores in the overall scale. Conclusion: The results suggest that public health campaigns should take into account the generational differences in COVID‐19 vaccination hesitancy to achieve higher levels of vaccine acceptance, including amongst healthcare professionals and students. Impact: Vaccination is the most effective strategy to tackle the COVID‐19 pandemic. The advice of health professionals strongly influences vaccination willingness in the general population. A consideration of the generational patterns in the COVID‐19 vaccination hesitancy of healthcare workers and students may increase vaccination uptake in these populations, which in turn may lead to greater public acceptance of the vaccine.